Changes in Working Conditions in Hospitals During the COVID-19 Pandemic in the Evaluations of Doctors and Nurses - Emilia KRAJNAKOVA; Sergej VOJTOVIC (Communications of International Proceedings, 2022)
Despite the current problems in the health sector, including the COVID-19 pandemic, which affect the lack of medical personnel in health care facilities, their departure to other spheres of employment, guessing work in regions or cities with more advanced infrastructure, or migration for work abroad, the emphasis in state, public measures and in the management of health care, it is based on institutional policies and strategies. As a result, the importance of personnel measures and policies, which should equally contribute to the development of healthcare and the solution of its current problems, is reduced. The health care provision system consists of people, doctors, nurses, paramedics and other categories of medical personnel and are its important component. The focus of our analyzes is the evaluation of changes in the working conditions of the two most numerous categories of health workers, namely doctors and nurses, affected by the pandemic situation. The results of similar studies could contribute to the creation of personnel measures, to the balance of individual parts of the policies and strategies of the healthcare system, and to the solution of its current problems. The main task of this study is to find out the perception and evaluation of changes in the working conditions in hospitals of doctors and nurses during the pandemic, to compare and characterize the differences in their evaluations based on the specifics of their work, the necessary qualifications and education. The comparison and assessment of changes in the work of doctors and nurses is based on information obtained in the process of conducting an empirical survey, statistical processing of respondents' verbal expressions to the level of statistical values ​​and calculation of their reliability. Finding and justifying the differences in the assessment of changes in the working conditions of doctors and nurses during the pandemic is important for the creation of current personnel policies and measures in the health sector.
Keywords: Hospitals; doctors; job satisfaction; working conditions; COVID-19